Tax Compromise and Tax Amnesty Procedures Implementation - M. S. Syromiatnikova (Bulletin of Kharkiv National University of Internal Affairs)
The research is focused on the problems of legal regulation of certain procedures of tax compromise and tax amnesty. The scientific article`s relevance is justified because certain procedures of tax compromise and tax amnesty should contribute to the balance of legitimate interests of citizens and the state. The purpose of the study is to identify propositions for amending the current legislation of Ukraine, establishing the possibility of reaching a tax compromise or the introduction of a tax amnesty. Scientific works of Ukrainian researchers, laws, and regulations were used in the process of studying the problem.